2011
DOI: 10.1891/1933-3196.5.1.2
|View full text |Cite
|
Sign up to set email alerts
|

EMDR for Survivors of Life-Threatening Cardiac Events: Results of a Pilot Study

Abstract: This pilot study evaluated the effectiveness of eye movement desensitization and reprocessing (EMDR) in treating posttraumatic stress disorder (PTSD) symptoms and concomitant depressive and anxiety symptoms in survivors of life-threatening cardiac events. Forty-two patients undergoing cardiac rehabilitation who (a) qualified for the PTSD criterion "A" in relation to a cardiac event and (b) presented clinically significant PTSD symptoms were randomized to a 4-week treatment of EMDR or imaginal exposure (IE). Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 48 publications
1
38
0
3
Order By: Relevance
“…Reviewing the literature clearly indicated that EMDR is effective in various anxiety disorders, including PTSD [18][19][20], social anxiety [21][22][23][24], specific phobia [25] and reducing symptoms of anxiety in other anxiety disorders [26][27][28][29]. However, few studies have been conducted on the effectiveness of EMDR for the treatment of GAD and its main symptoms -pathological worry.…”
mentioning
confidence: 99%
“…Reviewing the literature clearly indicated that EMDR is effective in various anxiety disorders, including PTSD [18][19][20], social anxiety [21][22][23][24], specific phobia [25] and reducing symptoms of anxiety in other anxiety disorders [26][27][28][29]. However, few studies have been conducted on the effectiveness of EMDR for the treatment of GAD and its main symptoms -pathological worry.…”
mentioning
confidence: 99%
“…Arabia, et al (2011) studied the effect of eye movement desensitization and reprocessing (EMDR) treatment on the post-trauma stress disorder (PTSD) and symptoms of anxiety and depression in the survivors with life-threatening cardiac events. The results showed that EMDR was an effective treatment in order to reduce the symptoms of PTSD, depression and anxiety, which can be occurred followed by the life-threatening cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that EMDR was an effective treatment in order to reduce the symptoms of PTSD, depression and anxiety, which can be occurred followed by the life-threatening cardiac events. The EMDR treatment could substantially reduce the level of significance of all the variables more than the exposure therapy (Arabia et al, 2011). Therefore, in patients with cardiac events, the treatment of anxiety, depression, and the symptoms of PTSD, can improve the quality of life in all aspects of patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…When treating PTSD with EMDR, comorbid depression improves in almost all cases and EMDR appears to be better at treating this than imaginal exposure (Arabia, Manca, & Solomon, 2011), waiting list controls (Hogberg et al, 2007;B. O. Rothbaum, 1997), standard care (Marcus, Marquis, & Sakai, 1997), fluoxetine or placebo pills (van der Kolk et al, 2007).…”
Section: Ptsd With Comorbid Depressionmentioning
confidence: 99%
“…Without a statistical sample size calculation one cannot be sure, and the standard care treatment in that study was extremely variable. Two studies call themselves pilots (Arabia et al, 2011;Ironson et al, 2002) so here a small sample size is to expected.…”
Section: Ptsd With Comorbid Depressionmentioning
confidence: 99%